(untitled) (Journal of actual problems of jurisprudence, 2025)
The article addresses several challenges in copyright protection within the digital landscape. The topic is particularly relevant given the expansive capabilities of modern information and communication technologies, which continually introduce risks to the rights of authors and copyright holders in science, literature, and art shared on the global web. In this context, providers—acting as information intermediaries—play a central role in online interactions, yet many countries’ laws have gaps in regulating their status and responsibilities. This study focuses on protecting authors’ rights on the Internet and clarifying the legal status and responsibilities of information intermediaries in Kazakhstan. The article aims to pinpoint deficiencies in the regulation of intermediary activities in Kazakhstan and to suggest legislative improvements. To meet these objectives, both general scientific and specialized research methods were employed. The novelty of this topic lies in the fact that Kazakhstan’s legal framework does not yet define the role of information intermediaries or their involvement in copyright protection on the Internet, and there is a lack of academic literature on this subject. This article is among the first to explore these issues. Key conclusions emphasize the need for a structured legal framework in Kazakhstan that defines information intermediaries, along with the scope and limits of their liability in cases of copyright infringement on the Internet. Keywords: copyright, copyright infringement, global network, information society, information intermediary, provider, DMCA, responsibility of information intermediaries.